Ultrasonic Assisted Synthesis of Graphene Based PbSe Nanocomposite with Enhanced Photocatalytic Activity - Zhu, Lei; Jo, Sun-Bok; Ye, Shu; Ullah, Kefayat; Oh, Won-Chun (Asian Journal of Chemistry, 2014)
In this article, we report a novel composite PbSe–graphene nanocomposite synthesis via facile ultrasonic assisted method. The structural and physicochemical properties of PbSe-graphene composite are further characterized by X-ray diffraction, scanning electron microscopy with an energy dispersive X-ray analysis. The photocatalytic activity of PbSe-graphene was evaluated by measuring the photocatalytic degradation of organic pollutants such as methylene blue, industrial dyes such as Texbrite BA-L (TBA) under visible light. The photocatalytic degradation was analyzed using UV/visible spectrophotometer. The kinetic studies were also conducted to determine the order and the rate of the photocatalytic degradation of the organic dyes.